Using a Delphi process to determine optimal care for patients with pancreatic cancer. Issue 2 (21st January 2016) - Burmeister, Elizabeth A; Jordan, Susan J; O'Connell, Dianne L; Beesley, Vanessa L; Goldstein, David; Gooden, Helen M; Janda, Monika; Merrett, Neil D; Wyld, David; Neale, Rachel E; ,
Abstract: Aim: Overall 5‐year survival for pancreatic cancer is ∼5%. Optimizing the care that pancreatic cancer patients receive may be one way of improving outcomes. The objective of this study was to establish components of care which Australian health professionals believe important to optimally manage patients with pancreatic cancer. Methods: Using a Delphi process, a multidisciplinary panel of 250 health professionals were invited to provide a list of factors they considered important for optimal care of pancreatic cancer patients. They were then asked to score and then rescore (from one [no importance/disagree] to 10 [very important/agree]) the factors. The mean and coefficient of variation scores were calculated and categorized into three levels of importance. Results: Overall, 63 (66% of those sent the final questionnaire; 25% of those initially invited) health professionals from nine disciplines completed the final scoring of 55 statements/factors encompassing themes of presentation/staging, surgery and biliary obstruction, multidisciplinary team details and oncology. Mean scores ranged from 3.7 to 9.7 with the highest related to communication and patient assessment. There was substantial intra‐ and interdisciplinary variation in views about MDT membership and roles. Conclusion: Overall, the opinions of Australian health professionals reflect international guideline recommended care; however, they identified a number of additional factors focusing on where patients should be treated, the importance of clear communication and the need for multidisciplinary care which were not included in current clinical practice guidelines. Differences in priorities between specialty groups were also identified.